Proteomic and metabolomic revealed the effect of shading treatment on cigar tobacco - Yan, Tongjing; Cai, Bin; Li, Fangyou; Guo, Dong; Xia, Changjian; Lv, Hongkun; Lin, Beisen; Gao, Huajun; Geng, Zhaoliang (Frontiers in Plant Science, 2024)
Shading or low light conditions are essential cultivation techniques for cigar wrapper tobacco leaves production, yet their impact on protein and metabolic regulatory networks is not well understood. In this study, we integrated proteomic and metabolomic a nalyses to uncover the potential molecular mechanisms affecting cigar tobacco leaves under shading treatment. Our findings include: (1) Identification of 780 significantly differentially expressed proteins (DEPs) in the cigar wrapper tobacco leaves, comprising 560 up-regulated and 220 down-regulated proteins, predominantly located in the chloroplast, cytoplasm, and nucleus, collectively accounting for 50.01%. (2) Discovery of 254 significantly differentially expressed metabolites (DEMs), including 148 up -regulated and 106 down-regulated metabolites. (3) KEGG pathway enrichment analysis revealed that the mevalonate (MVA) pathway within 'Terpenoid backbone biosynthesis' was inhibited, leading to a down -regulation of 'Sesquiterpenoid and triterpenoid biosynthes is'. Conversely, the 2-Cmethyl-D-erythritol 4-phosphate (MEP) pathway was enhanced, resulting in an up-regulation of 'Monoterpenoid biosynthesis', 'Diterpenoid biosynthesis', and 'Carotenoid biosynthesis', thereby promoting the synthesis of terpenoids such as carotenoids and chlorophylls. Simultaneously, the Calvin cycle in 'Carbon fixation in photosynthetic organisms' was amplified, increasing photosynthetic efficiency. These results suggest that under low light conditions, cigar tobacco optimizes photosynthetic efficiency by reconfiguring its energy metabolism and terpenoid biosynthesis. This study contributes valuable insights into protein and metabolic analyses, paving the way for future functional studies on plant responses to low light.